Gas hydrate and free gas detection using seismic quality factor estimates from high-resolution P-cable 3D seismic data - Singhroha, Sunny; Bünz, Stefan; Plaza-Faverola, Andreia; Chand, Shyam (Interpretation, 2015)
Source at http://dx.doi.org/10.1190/INT-2015-0023.1 . Reuse is subject to Society of Exploration Geophysicists terms of use and conditions. We have estimated the seismic attenuation in gas hydrate and free-gas-bearing sediments from high-resolution P-cable 3D seismic data from the Vestnesa Ridge on the Arctic continental margin of Svalbard. P-cable data have a broad bandwidth (20–300 Hz), which is extremely advantageous in estimating seismic attenuation in a medium. The seismic quality factor (Q), the inverse of seismic attenuation, is estimated from the seismic data set using the centroid frequency shift and spectral ratio (SR) methods. The centroid frequency shift method establishes a relationship between the change in the centroid frequency of an amplitude spectrum and the Q value of a medium. The SR method estimates the Q value of a medium by studying the differential decay of different frequencies. The broad bandwidth and short offset characteristics of the P-cable data set are useful to continuously map the Q for different layers throughout the 3D seismic volume. The centroid frequency shift method is found to be relatively more stable than the SR method. Q values estimated using these two methods are in concordance with each other. The Q data document attenuation anomalies in the layers in the gas hydrate stability zone above the bottom-simulating reflection (BSR) and in the free gas zone below. Changes in the attenuation anomalies correlate with small-scale fault systems in the Vestnesa Ridge suggesting a strong structural control on the distribution of free gas and gas hydrates in the region. We argued that high and spatially limited Q anomalies in the layer above the BSR indicate the presence of gas hydrates in marine sediments in this setting. Hence, our workflow to analyze Q using high-resolution P-cable 3D seismic data with a large bandwidth could be a potential technique to detect and directly map the distribution of gas hydrates in marine sediments